A Minimal Peptide Scaffold for [4Fe-4S]-Cluster Interrogation and Catalysis - Andrea, Bombana (2024)
The S-adenosyl-L-methionine (SAM) dependant superfamily of enzymes is capable of initiating a variety of biologically essential radical reactions. Likewise, bacterial-type ferredoxins mediate electron transfer to facilitate a broad range of biological redox processes. Both families of enzymes host a cubic [4Fe-4S]2+/+ motif that initiates and mediates the reactivity of these proteins.